Extraction of Nanofibrillated Cellulose from Water Hyacinth Using a High Speed Homogenizer - Supachok Tanpichai; Sirilak Mekcham; Chotirot Kongwittaya; Woraporn Kiwijaroun; Kasidit Thongdonsun; Chutidech Thongdeelerd; Anyaporn Boonmahitthisud (Journal of Natural Fibers, 2022)
Water hyacinth (Eichhornia crasspies) was used as a renewable cellulose source to prepare nanofibrillated cellulose (NFC). Due to the porous structure and low lignin content of water hyacinth, a 10 min-treatment time using the high-speed homogenization was sufficient to disintegrate nanofibers. The average width of the NFC treated for 40 min was 16.8 nm. With longer treatment times, a slight decrease in thermal stability of NFC was found while no changes in the crystallinity index of NFC were detected. Moreover, paper was formed from NFC with respect to mechanical treatment times. Results showed NFC treated with longer treatment times could prepare the paper with lower pore sizes between adjacent fibrils and porosity, resulting in higher wettability and mechanical properties. The contact angle of the 40 min-treated NFC paper was 36.0° while this contact angle result could not be measured from the samples of 0 min-treated NFC due to occurrence of large pores between fibers. The tensile strength of the NFC paper with 40 min-treatment time was ~18 times stronger than that of the 0 min-treated NFC paper. Mechanical energy consumption of the high-speed homogenization used to disintegrate NFC was also compared to that of the industrial defibrillation techniques.